A discussion about the stylistics of Samak-e Ayyar - محمّد غلامرضایی (تاریخ ادبیات)
Samak-e Ayyar is a folk tale, surviving from around the 6th or early 7th century, which was compiled by Faramarz bin Khodadad based on the narration of Sadaqa bin Abi al-Qasim Shirazi. The story revolves around the actions and behavior of one of the knights errant named Samak, and folk elements can be recognized in it at least from three aspects: the beliefs and culture of the common people, some narrative aspects, including the existence of random incidents and popular events and the language of the story. Mentioning fate in the events of the story, removing ambiguity from the reader's mind, the abundance of dialogue, multiple descriptions, are among the narrative features of the story. Samak-e Ayyar's prose is also the type of simple prose of the era, along with some linguistic obsolescence, both morphological and syntactical, and some features that could be specific to the language of the story; including a group of slang expressions, some of which go as far as cursing. Also, there are special adjectives in describing the objects and events of the story, some of which are used less in other texts. Saj’, reference to some verses and parables, and some images, especially wide and eloquent similes and irony, are also found in various places in the text, each of which is used in a specific position. Cultural expressions related to ancient Iran are among the important intellectual features in the story.